Gut Microbiota in Depression: A Focus on Ketamine - Wilkowska, Alina; Szałach, Łukasz Piotr; Cubała, Wiesław Jerzy (Frontiers in Behavioral Neuroscience, 2021)
According to the World Health Organization major depressive disorder is the leading cause of disability worldwide, and it is a major contributor to the overall global burden of disease. Pathophysiology of this common and chronic disease is still not completely understood. The gut microbiome is an increasingly recognized environmental factor that can have a role in depression acting through the microbiota-gut-brain axis. Available treatment for depression is still insufficient since 30% of patients are treatment resistant. There is an unquestionable need for novel strategies. Ketamine is an effective antidepressant in treatment resistant patients. It is suggested that the antidepressant effect of ketamine may be partially mediated by modification of gut microbiota. Here we present a review of data on gut microbiota in depression with special attention to the effect of ketamine on microbiome in animal models of depression. Presented reports are preliminary and still insufficient to draw firm conclusions, but further studies in this field might help to understand the role of the gut-brain axis in treatment of depression and be the ground for developing new effective treatment strategies.